The effect of acceptance and commitment therapy on the resilience of women experiencing spousal abuse - Fatemeh Khakshoor Mohammad Abadi; Sakineh Taherkhani; Abed Majidi; Azam Moslemi (Tehran University of Medical Sciences, 2023)
Background & Aim: In women experiencing intimate partner violence, resilience can serve as a protective factor against the worsening of psychological problems. Acceptance and Commitment Therapy has emerged as a potential means to enhance resilience in these individuals. The aim of this study is to determine the effect of Acceptance and Commitment Therapy on the resilience of women experiencing spousal abuse. Methods & Materials: This is a quasi-experimental study. A total of 80 women experiencing spousal abuse were selected through quota sampling from the women referring to the health houses affiliated to the Mashhad ol-Kube health center in Arak, Iran between 2020 and 2021. The participants were then divided into intervention and control groups using the block randomization method. The intervention group received the Acceptance and Commitment Therapy in eight sessions, lasting 90 minutes each, once a week. The data collection tools included a questionnaire on personal and health characteristics, the Revised Conflict Tactics Scale, and the Connor‐Davidson Resilience Scale. The Resilience Scale was completed by both groups one week and five weeks after the intervention. The data were analyzed through the SPSS software version 23 using descriptive statistics, independent t-test, Chi-square test, Fisher's exact test, and two-way repeated measures ANOVA. A significance level of P<0.05 was used to determine statistical significance. Results: The mean and standard deviation of the resilience score for the intervention group increased from 59.21±13.29 before the intervention to 64.31±11.27 and 72.34±10.49 in the post-test and follow-up periods. For the control group, these figures were 52.47±17.2, 51.94±14.72, and 52.47±15.3, respectively. Based on the results of the two-way repeated measures ANOVA, there was a statistically significant difference in the mean score of resilience between the intervention and control groups at the three time points examined (P<0.001). Conclusion: The implementation of Acceptance and Commitment Therapy can significantly improve the resilience of women experiencing spousal abuse. This intervention holds great potential for being incorporated into mental health improvement programs specifically designed for women who have experienced spousal abuse.